"There's a Camera Everywhere": How Citizen Journalists, Cellphones, and Technology Shape Coverage of Police Shootings - Walker, Denetra (Journalism practice, 2022)
Through the lens of gatekeeping, this study examines how an evolving technological landscape influences the way television news journalists cover the issue of deadly, highly-publicized police shootings in the United States. Through 10 in-depth interviews of television news journalists, the author analyzes how social media, cellphones, and citizen journalists shape this narrative. Themes include a change in speed and accessibility, accuracy, and a multi-layered challenge to police authority. Practical and theoretical implications on the future digital landscape covering this topic are discussed.